Development Strategies and Manpower Needs The Response of Southeast Asian Universities. Proceedings of the Workshop held in Vientiane, Laos, 15-17 December 1974 - Regional Inst. of Higher Education and Development, Singapore; Muhammadi; Regional Inst. of Higher Education and Development, Singapore ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The report of the Regional Institute of Higher Education and Development Workshop held in Vientiane, Laos, December 1974 is presented. The workshop focused on three main issues: national development strategies and high-level manpower needs; the responses of universities of high-level manpower requirements; and the employment of university graduates in Southeast Asia. (Author/LBH)
Availability: Regional Institute of Higher Education and Development, CSSDI Building, Heng Mui Keng Terrace, Singapore 5 ($7.50).
ERIC Note: For related studies, see HE 008 588-590.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Asian Studies; College Graduates; Conference Reports; Developing Nations; Educational Objectives; Employment; Foreign Countries; Higher Education; Labor Needs; Labor Utilization; National Programs; Political Issues; Universities; Asia (Southeast); Indochina -- Indonesia -- Malaysia -- Singapore -- Thailand; Speeches/Meeting Papers